PUBLIC POLICY OF THE DEVELOPMENT OF REGIONS IN UKRAINE: ASPECTS OF MECHANISM OF FORMATION AND IMPLEMENTATION - Lukisha R.T. (Pressing Problems of Public Administration, 2015)
The article says about the theoretical bases of formation public policy of the development of regions in Ukraine at risks. Given the analysis of the main aspects of functioning of this policy in context political, legal, financial and economic support.